Review Of The Emotional Disorder Theories In The Developmental Stage Of Adolescence. - Zeb, Aurang (International Journal of Rehabilitation and Special Education (IJRSE), 2021)
Emotions almost rule lives in every state of age, the difference is that of level of control which is highly effected by the situation faced by the individual. Emotions appear from the physiques of the individuals unintentionally. Adolescence is the most particular stage of life in which emotions develop positively or negatively. It is a descriptive study for which the primary data was collected from the research works of theorists. The different aspects of emotional disorders and disturbance in adolescence were reviewed and suggestions were given. All the stake holders i.e. School, parents and community around the developmental stage of adolescence are beneficiary of it. The study suggests emotional disorder is the combination of so many symptoms of emotional disturbance which spoils life, if not find in time, ignoring or mishandling it. Children in adolescence easily accept ecological effects, positive effects develop sound mind and negative drags towards negative impulses. There should be a balance and proper mechanism for class promotion, award distribution and other assignments of responsibilities among students so as to create a positive environment in school.